EVALUASI ANGGARAN PEMERINTAH DAERAH UNTUK MENGUKUR EFEKTIVITAS KINERJA KEUANGAN DAERAH (Studi Kasus Pada Pemerintah Daerah Provinsi Jawa Barat) - Salsa Nurul Safitri; Ahmad Syarief (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The occurrence of the Covid-19 pandemic caused the Province of West Java to experience difficulties in realizing its budget. This study will examine the performance of the West Java Regional Government's financial budget in the midst of the Covid-19 Pandemic by examining the West Java Regional Government Budget. This research method is descriptive with a quantitative approach. The data source used is secondary data in the form of the West Java Provincial Budget Realization Report for the 2020 and 2019 periods. Researchers will process and analyze the data manually using the formulas listed in Chapter III, which in detail will use the Proportional Analysis method, Efficiency Ratio , Effectiveness Ratio of Regional Revenue and Expenditure Revenue, Regional Financial Independence Ratio (RKKD), Activity Ratio (RA), and Fiscal Decentralization Ratio. The conclusion of this study is that in 2020 the West Java APBD experienced a decrease in the proportion of Operational Expenditures, Capital Expenditures, and Transfers. The PAD Efficiency Ratio shows the cost of collecting PAD is carried out efficiently. West Java Province is considered less capable in realizing PAD Revenue. The effectiveness ratio of Regional Expenditures in 2020 has increased by 1%. West Java Province is able to implement regional autonomy. West Java Province prioritizes its budget for Routine Expenditures and Assistance Expenditures. West Java Province PAD contributes greatly to all revenues Ratio.